Pengembangan Evaluasi Pembelajaran Interaktif Berbasis Bamboozle Games Menggunakan Metode Teams Games Tournament (TGT) pada Pembelajaran Aqidah Akhlak di SMA Ahmad Yani 2 Baureno - Istika, Amirah; Ayu, Intan (AJER: Advanced Journal of Education and Religion, 2025)
Aqidah Akhlak learning at SMA Ahmad Yani 2 Baureno still uses a monotonous lecture method, which reduces students’ interest and activeness. Academic supervision results also indicate that the use of media and teaching methods has not been optimal. To address this, the researcher developed both a learning medium and an evaluation tool based on Bamboozle Games using the Teams Games Tournament (TGT) method to make learning more interactive and enjoyable. This medium not only supports the delivery of material but also serves as an evaluation tool that enables teachers to directly assess students’ understanding through educational games. The research employed the R&D method with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation), involving 55 eleventh-grade students. Data were collected through observation, interviews, teacher and student response questionnaires, pre-tests, post-tests, and documentation. The results showed that the Bamboozle Games based TGT medium was highly valid according to material experts (97%) and media design experts (93%). Teacher responses reached 95% (very effective), and student interest was 83.63% (very high interest). The effectiveness of the medium was further evidenced by a significant increase in post-test scores compared to pre test scores, indicating that it can improve learning outcomes while serving as an engaging evaluation tool. Thus, the Bamboozle Games-based Teams Games Tournament (TGT) is effective in enhancing students’ motivation, activeness, and learning outcomes, while also providing an innovative alternative for Aqidah Akhlak learning in the digital era.